Relationship between epipelon, epiphyton and phytoplankton in two limnological phases in a shallow tropical reservoir with high Nymphaea coverage - dos Santos, Thiago Rodrigues; Castilho, Maria Carolina [UNESP]; Henry, Raoul [UNESP]; Ferragut, Carla (Springer Nature, 2020)
Macrophytes and phytoplankton are recognized as having roles in determining alternative stable states in shallow lakes and reservoirs, while the role of periphyton has been poorly investigated. Temporal and spatial variation of phytoplankton, epipelon and epiphyton was examined in a shallow reservoir with high abundance of aquatic macrophytes. The relationships between algae communities and abiotic factors, macrophyte coverage and zooplankton density were also analyzed. Monthly sampling was performed in three zones of the depth gradient of the reservoir. Two phases of algal dominance were found: a phytoplankton phase and epipelon phase. The phase of phytoplankton dominance was characterized by high macrophyte coverage. Rotifera was the dominant zooplankton group in all the zones. Flagellate algae were dominant in phytoplankton, epipelon and epiphyton. Macrophyte coverage was found to be a predictor for algal biomass. Changes in biomass and species composition were associated with macrophyte cover variation, mainly the Nymphaea. In addition to the abiotic factors, the macrophyte coverage was a determining factor for changes to the algal community, contributing to the alternation between dominance phases of phytoplankton and epipelon. The macrophyte–phytoplankton–periphyton relationship needs to be further known in shallow reservoirs, especially the role of epipelon as an alternate stable state.
Keywords: Algal communities; Autotroph interactions; Macrophyte coverage; Pelagic and littoral zones; Zooplankton